Pengembangan Multimedia Interaktif Galeri Budaya Pada Materi Keberagaman Budaya dan Suku di Jawa Timur - Nur Lillah Hidayati; Wahyudi Wahyudi; Sutrisno Sahari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This research was motivated by the results of observations in class IV of SDN Kraton regarding cultural and ethnic diversity in East Java, it was found that teachers rarely used media that was varied and less interesting for students. Research objectives Develop an interactive multimedia cultural gallery on cultural and ethnic diversity in East Java for fourth grade students at SDN Kraton Mojo? Testing the practicality of an interactive multimedia cultural gallery on cultural and ethnic diversity material in East Java for fourth grade students at SDN Kraton Mojo? Testing the effectiveness of the interactive multimedia cultural gallery on cultural and ethnic diversity material in East Java for fourth grade students at SDN Kraton Mojo? This research uses the Research and Development (R&D) research method with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). Research and development of interactive multimedia in the cultural gallery on cultural and ethnic diversity in East Java has met the criteria with the conclusion that the interactive multimedia in the cultural gallery is valid, practical and very effective for use in the learning process.